1999
DOI: 10.1001/archpsyc.56.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Brain Asymmetry as a Biological Substrate of Emotions in Patients With Panic Disorders

Abstract: These data support the hypothesis that patients with panic disorder are characterized by greater activation of a right frontal avoidance-withdrawal system in negatively valenced situations. The findings are interpreted as biological evidence for a disturbed cortical processing in patients with panic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
146
2
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(165 citation statements)
references
References 51 publications
(59 reference statements)
14
146
2
3
Order By: Relevance
“…In clinical samples, asymmetrical frontal activity has often~Allen et al, 1993Gotlib et al, 1998;, 1991Wiedemann et al, 1999! but not ubiquitously~Reid et al, 1998!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical samples, asymmetrical frontal activity has often~Allen et al, 1993Gotlib et al, 1998;, 1991Wiedemann et al, 1999! but not ubiquitously~Reid et al, 1998!…”
Section: Discussionmentioning
confidence: 99%
“…Several authors~e.g. Davidson, 1998HarmonJones & Allen, 1997, 1998Sutton & Davidson, 1997;Wiedemann et al, 1999! have suggested that these frontal asymmetries tap not positive or negative affect per se, but a broader motivational tendency towards approach-related or withdrawal-related behaviors and emotions.…”
mentioning
confidence: 99%
“…(3) Converging evidence points toward a crucial role of unflexible and maladaptive processing of emotional stimuli in the pathogenesis of anxiety and anxiety disorders: anxiety-related emotional stimuli are rated as more threatening by patients than by control individuals and seem to be processed differently within the limbic-medial prefrontal circuit, partly driven by genetic factors (eg, Domschke et al, 2006Domschke et al, , 2008bDomschke and Dannlowski, 2010;Etkin, 2010;Lang and Cuthbert, 1984;Mathews, 1993;Mühlberger et al, 2006Mühlberger et al, , 2007Pauli et al, 1996;Wiedemann et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Wiedemann Showed frontal brain waves' asymmetry as a biological substrate of emotions in patients with panic disorders [12]. Biriukova Showed clinical and neurophysiological efficacy of neurofeedback in the combined therapy of anxiety disorders resistant to psychopharmaco therapy [13]. La Vaque and colleagues in evaluating neurofeedback treatment of anxiety disorders showed it was an efficacious treatment [14].…”
Section: Discussionmentioning
confidence: 99%